Preparation and characterization of self-healing furan-terminated polybutadiene (FTPB) based on Diels–Alder reaction. Issue 51 (30th September 2021) - Xia, Min; Zhang, Yanjie; Na, Qing; Guo, Tao; Zhang, Minghao; Qi, Zhenyu; Liu, Ningning; Yang, Fanzhi; Luo, Yunjun; Yang, Wei
Abstract : Thermoreversible self-healing process of FTPB-DA. Abstract : Cracks generated in energetic composites will affect their mechanical properties and increase the risk of explosion when they are exposed to external stimuli. Therefore, self-healing properties of energetic composites have always been at the forefront of research in the field of high-performance energetic composites. Hydroxyl-terminated polybutadiene (HTPB) is a kind of binder widely used in propellants. A novel furan-terminated polybutadiene (FTPB) was synthesized by the reaction of NCO-terminated polybutadiene (IPDI-HTPB-IPDI) with furfuryl amine, and then self-healing binder films were obtained based on the DA adduct (FTPB-DA) through the reaction of furan with bismaleimide. The results show that FTPB-DA will transform into FTPB and BMI at 120 °C and recrosslinked at 60 °C to form FTPB-DA again, which gives it self-healing properties and the healing efficiency can reach 92.3%. Then, by adjusting the ratio of –NCO/–OH during the preparation process, we prepared self-healing binders with different DA adduct contents, and further studied the influence of DA adduct content on the mechanical properties and self-healing performance.